The dragon and the iron factory - Kaminski, Leah (Secret Society of Monster Hunters., 2021)
Tío Hector sends Fiona, Amy, and Elena back in time to the 1940s and a huge shipyard in Bath, Maine. They meet Rosie the Riveter and the other women workers building huge ships to fight in World War II, but the trio needs to find a huge red dragon before history learns of its existence.